Hotspots, Frontiers, and Emerging Trends of Superabsorbent Polymer Research: A Comprehensive Review - Yang, Minmin; Wu, Jihuai; Graham, Geoffrey M.; Lin, Jianming; Huang, Miaoliang (Frontiers in Chemistry, 2021)
Superabsorbent polymer (SAP) is a kind of functional macromolecule with super-high water absorption and retention properties, which attracts extensive research and has wide application, especially in the areas of hygiene and agriculture. With reference to the Web of Science database, the SAP research literature from 2000 to 2019 is reviewed both quantitatively and qualitatively. By examining research hotspots, top research clusters, the most influential works, the representative frontier literature, and key emerging research trends, a visual panorama of the continuously and significantly increasing SAP research over the past 2 decades was presented, and issues behind the sharp increase in the literature were discovered. The findings are as follows. The top ten keywords/hotspots headed by hydrogel highlight the academic attention on SAP properties and composites. The top ten research themes headed by clay-based composites which boast the longest duration and the strongest impact have revealed the academic preference for application rather than theoretical study. Academically influential scholars and research studies have been acknowledged, and the Wu group was at the forefront of the research; however, more statistically significant works have been less detected in the last 10 years despite the sharper increase in publications. Hydrogel, internal curing, and aerogel are both current advances and future directions.